Monday

September 1, 2014

September 1, 2014

Posted by **Rose** on Monday, October 9, 2006 at 3:50pm.

(cscX-cotX)^2=1-cosX/1+cosX

_______

sorry i cant help you

(cscX-cotX)=1/sinX - cosX/sinX = (1-cosX)/sinX

If you square this you have (1-cosX)^2/(sinX)^2

Now use (sinX)^2 = 1 - (cosX)^2 to get

(1-cosX)^2 / 1 - (cosX)^2 =

[(1-cosX)*(1-cosX)]/[(1 - cosX)*(1 + cosX)

Then simplify.

**Answer this Question**

**Related Questions**

drwls - My previous question: Verify that (secx/sinx)*(cotx/cscx)=cscx is an ...

trig - express this in sinx (1/ cscx + cotx )+ (1/cscx- cotx) i got 2sinx is ...

trigonometry - can i use factoring to simplify this trig identity? the problem ...

Trigonometry. - ( tanx/1-cotx )+ (cotx/1-tanx)= (1+secxcscx) Good one! ...

Trig........ - I need to prove that the following is true. Thanks (cosx / 1-sinx...

Math - Im really struggling with these proving identities problems can somebody ...

Pre-Calc - Trigonometric Identities Prove: (tanx + secx -1)/(tanx - secx + 1)= ...

Trigonometry Check - Simplify #3: [cosx-sin(90-x)sinx]/[cosx-cos(180-x)tanx] = [...

Math - I'm only aloud to manipulate one side of the problem and the end result ...

Math 12 - Simplify #1: cscx(sin^2x+cos^2xtanx)/sinx+cosx = cscx((1)tanx)/sinx+...